Beyond Compliance: Pengungkapan CSR dan Industry-Adjusted Firm Performance pada Perusahaan Pertambangan Indonesia - Trisna Gayatri (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study examines the effect of CSR disclosure on the Industry-Adjusted Firm Performance of Indonesian mining companies. Firm performance is measured using industry-adjusted return on assets (Adj. ROA), calculated as a firm’s ROA minus the average ROA of sample firms in the same subindustry and year. The sample consists of 30 mining companies observed from 2017–2024. CSR disclosure is measured through content analysis of 85 GRI Standards indicators, with scores assigned based on the completeness of the disclosed information. The findings indicate that CSR disclosure is not significantly associated with Adj. ROA, and this conclusion remains consistent in the sensitivity analysis. These results suggest that broader CSR disclosure does not directly lead to superior profitability relative to other firms in the same subindustry. In the mining sector, CSR disclosure may primarily serve as a mechanism for accountability, stakeholder relationship management, and the maintenance of corporate legitimacy.